Writer’s „Think Painting“ Imereti (According to Davit Kldiashvili’s Work) - Gogoladze, Tamar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Davit Kldiashvili (1862-1931) dedicated his entire life and literary career to Imereti, a picturesque region of Georgia. This article aims to explore how Kldiashvili portrayed Imereti in his works and how Grigol Robakidze analyzed Kldiashvili’s literary contributions. Since the 1860s, Georgian literature has grappled with the question of Imereti’s distinctiveness within the broader Georgian cultural landscape. Davit Kldiashvili, himself a native son of Imereti and a prolifific writer, articulated this uniqueness both in his artistic creations and memoirs. This article seeks to depict the portrait of Imeretian characters as portrayed by Kldiashvili. Grigol Robakidze, another prominent writer and literary critic born in Imereti, reflflects on Kldiashvili’s artistic style in his essay „Davit Kldiashvili“. Robakidze notes that despite Kldiashvili’s strict adherence to realism, the characters he created possess a distinctive aura. While Kldiashvili observes the moods and nuances of his relatives and acquaintances in works like „On the Road of My Life“, Robakidze critically examines Kldiashvili’s oeuvre to elucidate his artistic genius. In the concluding section of his essay, Robakidze emphasizes, „If uniqueness were to be rewarded, Imereti would undoubtedly claim the prize fifirst“. This statement underscores the exceptional nature of Imereti and its inhabitants, as perceived by Robakidze. He fifinds irreproducibility in the region’s landscapes, fauna, and most signifificantly, its people, whom Kldiashvili portrays with simplicity, ease, and a touch of humorous melancholy against the backdrop of Georgia’s societal challenges during that era. Ultimately, this article aims to highlight the distinctive perspectives of these two writers, both deeply connected to their native Imereti. Their writings serve as keys to unlocking the essence of Imereti and its people, enriching Georgian literature with their nuanced portrayals and keen observations.